Analysis of product-service solution inventory record for Malaysian palm oil argibusiness - Zaitun, Zainal Abidin; Siti Zubaidah, Ismail (Penerbit UMP, 2020)
Product-Service System (PSS) inventory control for Palm Oil Plantation Company and developing one software application named as inventory record to help the management for managing the inventory control of the company. This research deals with the study ofPSS and inventory control at Company A which is a Malaysian palm oil plantation company. The aims of this research are to describe and analyzehow Product-Service Solution Inventory. The palm oil industry is one of the well-known industries in Malaysia that provide the most prominent contribution to Malaysia’s economy. PSS is a managing system that combining product and service in one system. PSS could not be running smoothly when the inventory of product and service are managed in separate interface systems which is by using manual inventory control like Microsoft Excel and handwriting documentation. In order to make PSS inventory control easier, and systematic, an inventory application system is developed. This research is focusing on developing PSS inventory record for fertilizer and pesticide at the Company A. This record will be using Microsoft Visual Basic 6 which could help in decision and calculation making for product and service of palm oil plantation.